Wonder - Palacio, R J (London Corgi : Random House Children's Publishers, 2014)
Whatever you're thinking, it's probably worse.'Auggie wants to be an ordinary ten-year-old. He does ordinary things - eating ice cream, playing on his Xbox. He feels ordinary - inside. But ordinary kids don't make other ordinary kids run away screaming in playgrounds. Ordinary kids aren't stared at wherever they go
English stories
2 13
Keywords: English stories